2006
DOI: 10.1016/j.devcel.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent Flk-1+ Cardiovascular Progenitor Cells Give Rise to the Cardiomyocyte, Endothelial, and Vascular Smooth Muscle Lineages

Abstract: Cell-tracing studies in the mouse indicate that the cardiac lineage arises from a population that expresses the vascular endothelial growth factor receptor 2 (VEGFR2, Flk-1), suggesting that it may develop from a progenitor with vascular potential. Using the embryonic stem (ES) cell differentiation model, we have identified a cardiovascular progenitor based on the temporal expression of the primitive streak (PS) marker brachyury and Flk-1. Comparable progenitors could also be isolated from head-fold stage embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
676
1
17

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 685 publications
(738 citation statements)
references
References 53 publications
(75 reference statements)
44
676
1
17
Order By: Relevance
“…Eomes overexpression also promoted the appearance of endothelial cells (expressing VE-cadherin and CD31; Fig 1D,E,J) and smooth muscle cells (expressing smooth muscle actin; Fig 1F,G,K and supplementary Fig S2B online). Altogether, the three types of cells derived from multipotent cardiovascular progenitors (MCPs) [27,[35][36][37] were massively increased following Eomes expression in DDM, although we cannot rule out that some endothelial and smooth muscle cells could also derive from other progenitors (such as the hemangioblasts [38] that could also be induced following Eomes expression). We and others have recently demonstrated that a combination of monoclonal antibodies (Flk1/Pdgfra) can be used to isolate the earliest Mesp1 expressing MCPs arising during ESC differentiation [16,27].…”
Section: Results and Discussion Eomes Promotes Cardiogenesis In Escmentioning
confidence: 99%
“…Eomes overexpression also promoted the appearance of endothelial cells (expressing VE-cadherin and CD31; Fig 1D,E,J) and smooth muscle cells (expressing smooth muscle actin; Fig 1F,G,K and supplementary Fig S2B online). Altogether, the three types of cells derived from multipotent cardiovascular progenitors (MCPs) [27,[35][36][37] were massively increased following Eomes expression in DDM, although we cannot rule out that some endothelial and smooth muscle cells could also derive from other progenitors (such as the hemangioblasts [38] that could also be induced following Eomes expression). We and others have recently demonstrated that a combination of monoclonal antibodies (Flk1/Pdgfra) can be used to isolate the earliest Mesp1 expressing MCPs arising during ESC differentiation [16,27].…”
Section: Results and Discussion Eomes Promotes Cardiogenesis In Escmentioning
confidence: 99%
“…Additionally, the typically very low yield of cardiac differentiation of hESCs also makes the harvesting of enough purified proteins from hESC-CMs even more difficult. Recent protocols to substantially improve the yield of CMs have been reported [35][36][37] but the heterogeneity of chamber-specific CMs have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Murine heart development starts during gastrulation when cells of the anterior mesoderm form a common cardiovascular progenitor cell (CPC) population (Kattman et al, 2006;Moretti et al, 2006;Yang et al, 2008). When development proceeds, this cell population gives rise to two different cardiac lineages, the first heart field (FHF) and the second heart field (SHF) lineage, respectively.…”
Section: Introductionmentioning
confidence: 99%